2017
DOI: 10.1016/j.jmapro.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Online measuring the electrical resistivity of molten nugget of stainless steel in resistance spot welding

Abstract: The variation characteristics of electrical resistivity of the parent metal can improve in-depth understanding of the resistance spot welding (RSW) process. According to the characteristic of RSW process and the physical principle of electrical resistivity, a comprehensive mathematical description of the electrical resistivity measurement of the molten nugget can be obtained. Then a series of corresponding experiments, including the RSW operation to obtain the dynamic resistance, online temperature measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Resistance spot welding (RSW) method is a propagated utilized joining process in metals welding with a thin thickness to structure manufacturing, particularly in the automotive, ship-building, and lightweight industries 1,2 . At present, the industries are aiming to minimize the cost together weight with a compromise between of high performance and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance spot welding (RSW) method is a propagated utilized joining process in metals welding with a thin thickness to structure manufacturing, particularly in the automotive, ship-building, and lightweight industries 1,2 . At present, the industries are aiming to minimize the cost together weight with a compromise between of high performance and safety.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature field and microstructure characteristics of these two joints were studied through simulation and experiments. Kang Zhou et al [19] found that the electrical resistivity of the molten nugget was theoretically and experimentally deduced, according to detailed theoretical analyses based on the principle of electrical resistivity and the resistance spot welding process. Yi Luo et al [20] calculated the dynamic resistance based on the welding current and electrode voltage detected in resistance spot welding and studied the thermal effects of nugget growth during nugget forming.…”
Section: Introductionmentioning
confidence: 99%